Petrogenesis of metaluminous and peraluminous granitoids from Garga-Sarali zone : evidence of I- and S-type sources (central African fold belt in Cameroon) - Isaac , Daama; Gbambie Isaac Bertrand , Mbowou; Dagwaï , Nguihdama; Ismaïla , Ngounouno (International Journal of Advanced Geosciences, 2024)
The Garga-Sarali granitoids outcrop from a metamorphic basement in the central-eastern part of the Central Cameroonian Domain of the Central African fold belt in Cameroon, and are petrographically very complex. They can be divided into two types : (1) Granodiorites of metaluminous type-I, with a fine-grained porphyritic variant texture, consisting of quartrz + orthoclase + microcline + plagioclase + biotite + zircon + oxides ± apatite; (2) and two-mica granites of hyper-aluminous type-S, with a grainy texture, consisting of the same quartzo + k-feldspars + biotite + cordierite ± apatite. These formations both belong to a calc-alkaline-subalkaline, hyper-potassic to shoshonitic signature, and to the tectonic domains of volcanic arc granites. Their emplacement is intimately linked to a crustal parent magma (metagrauwackes and metabsalt-tonalites) that imbibed through the openings in the post-orogenic pan-African lithospheric constraints. Their La/Yb ratio, with (La/Sm)n ranging from 2.18-5.75 ppm, reflects their richness in LREE, and the average Eu/Eu*=0.666 ppm suggests that the residual magma was supersaturated with silica.